ANALYSIS OF STUDENT EXPERIENCES IN TOURISM EVENT PROUREMENT AT THE TOURISM POLYTECHNIC, MAKASSAR CITY - Nur Athirah; Hiro Rifqoh Suardy (Politeknik Pariwisata Makassar, 2025)
This study aims to examine the experiences of students in the Convention and Event Management Study Program in organizing events at the Makassar Tourism Polytechnic. The primary focus of the study is to identify the obstacles and challenges faced by students during the planning, coordination, and implementation of events, as well as the strategies they employ to overcome these obstacles, ensuring the events run smoothly and achieve their intended goals. The method employed is a qualitative approach, involving data collection through in-depth interviews and participatory observation of students actively involved in the event committee, conducted in 2025. The study's results reveal that the main obstacles faced by students include limited funds as a source of financing, difficulties in finding sponsors to support activities, ineffective communication and coordination among committee members, and suboptimal time management in preparing for events. To overcome these problems, students implemented various strategies, including careful and structured planning, creating detailed work timelines, holding regular coordination meetings, utilizing digital communication groups such as WhatsApp to facilitate coordination, and distributing tasks clearly and organized. The evaluation of the event's implementation was conducted comprehensively, involving the entire committee and supervising lecturers. This study recommends strengthening training and improving event management competencies in the academic curriculum, increasing the active role of lecturers and practitioners in mentoring and evaluation, and developing an event management information system to support the effectiveness and efficiency of event management. In conclusion, the success of events organized by students greatly depends on the mastery of structured managerial skills and synergistic collaboration between various related parties. The practical experience gained from organizing these events not only improves students' professional competencies but also contributes positively to the sustainable development of local tourism.